2022
DOI: 10.3390/su14042201
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of a Hybrid Solar PV/BG-Powered Heterogeneous Network

Abstract: The increased penetration of renewable energy sources (RESs) along with the rise in demand for wireless communication had led to the need to deploy cellular base stations powered by locally accessible RESs. Moreover, networks powered by renewable energy sources have the ability to reduce the costs of generating electricity, as well as greenhouse gas emissions, thus maintaining the quality of service (QoS). This paper examines the techno-economic feasibility of developing grid-tied solar photovoltaic (PV)/bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Calculating the HC gives the assessment of PV capacity to be integrated into the grid without violating the grid code. A few studies, including [26][27][28] identified the necessity of considering critical technical scenarios along with the investigation of the economic feasibility of industry operations. However, to the best of the authors' knowledge, the existing literature did not carry out detailed studies taking the issues of varying operation scenarios under system disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Calculating the HC gives the assessment of PV capacity to be integrated into the grid without violating the grid code. A few studies, including [26][27][28] identified the necessity of considering critical technical scenarios along with the investigation of the economic feasibility of industry operations. However, to the best of the authors' knowledge, the existing literature did not carry out detailed studies taking the issues of varying operation scenarios under system disturbances.…”
Section: Introductionmentioning
confidence: 99%